(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the current state, challenges, and future prospects of developing digital technologies in Uzbekistan. It emphasizes the importance of digital transformation as a key factor for economic growth, education, healthcare, and governance. The paper examines national initiatives, particularly the “Digital Uzbekistan – 2030” program, highlighting both the achievements and obstacles in the process of digitalization. Special attention is given to issues of digital literacy, infrastructure gaps, and cybersecurity. The study concludes that despite existing challenges, Uzbekistan has significant opportunities to become a regional leader in digital technologies through innovation, youth engagement, and international cooperation.